Visakhavijaya, a study - Ramakrishna Pillai, Poovattoor, 1935-2006 (Poovattor Ramakrishna Pillai : For copies, Anitha Publications, 1990)
Study of Viśākhavijaya, Sanskrit epic by Kēraḷavarmma, 1844-1917.